OXYGEN REACTIVE SPECIES EFFECTIVELY SCAVENGED BY VARIOUS EXTRACTS OF LEAVES AND BARK OF EUCALYPTUS GLOBULUS - Sarwar, Abid; Saeed, Muhammad Khalid; Zahra, Naseem; Ullah, Najeeb; Aziz, Tariq; Alharbi, Metab; Alshammari, Abdulrahman; Alasmari, Abdullah F. (Journal of the Chilean Chemical Society, 2023)
Eucalyptus globulus is belong to a family of Myrtaceae and one of the important medicinal plants. Eucalyptus leaf extract is a used as an antioxidant in various food additives. With this in mind, fresh leaves and bark of eucalyptus were taken dried, grinded and extractive contents were measured. Various extracts of leaf and bark of Eucalyptus globulus were made and used for the estimation of phytochemicals, total flavonoids or phenolic content, and for determination of in-vitro antioxidant activity. The highest extractive contents of E. globulus leaf were 4.75±0.25% and bark 7.95±0.50% with water. Phytochemical tests showed that the water extracts of the leaves and bark contain alkaloids, flavonoids, glycosides, terpenoids, steroids, and saponins, while there are no cardiac glycosides and anthraquinones. Phenols and flavonoids studies have shown that leaves extract contain significant amounts of phenols and flavonoids (152.6±1.5 mg/g gallic acid equivalent; 42.30±0.7 mgQE/g dry weight) and 120.3±1.1 mg/g gallic acid equivalent 29.2±0.5 mgQE/g dry weight in water extract of bark. All extracts exhibited considerable DPPH (2,2-diphenyl-1-picrylhydrazyl), with the highest percentage inhibition in aqueous leaves extracts 87.41±1.2 (IC50 58.88±2.15 µg/ml), while lower in chloroform 48.39±0.6 (IC50 88.22±2.90 µg) /ml), than bark water extract: 80.15±1.1 (IC50 63.43±2.25 µg/ml; chloroform extract: 42.02±0.5 (IC50 90.10±2.95), While the percentage inhibition of BHT was 92.8±1.3, the IC50 was 29.70±1.55 µg/ml was detected at 250 µg/ml concentration. Reducing capacity when compared in leaves and bark, the following order was observed: water extract˃ethanol extract˃EtOH-H2O˃methanol extract˃MeOH-H2O extract˃chloroform extract. This study has confirmed that water extracts of E. globulus leaves and bark have the highest antioxidant activity and may contain high amounts of flavonoids and phenolics.